What Holds Women Back in Academic Leadership Positions: A Case Study in The Gulf Cooperation Council (GCC) - Jaradat, Maram Salah (Advances in Social Sciences Research Journal, 2019)
The purpose of this study was to discover the challenges preventing women from advancing in academic leadership positions. It also investigated the scope of support and acceptance of women as leaders in their workplace including administration. The study was conducted in a private university in the United Arab Emirates using a quantitative online survey. The data were collected from 115 academic women including (68) working in administrative positions and (47) in non-administrative positions.. The results showed that the most significant challenges women in leadership positions face are lack of colleagues’ support (.515**), men not accepting women as leaders (.467**), society not accepting women as leaders (.389**) and lack of confidence in women (.389**).